Tedizolid, Faropenem, and Moxifloxacin Combination With Potential Activity Against Nonreplicating Mycobacterium tuberculosis - Srivastava, Shashikant; Cirrincione, Kayle N.; Deshpande, Devyani; Gumbo, Tawanda (Frontiers in Pharmacology, 2021)
Background. Mycobacterium tuberculosis [Mtb] could be present in different metabolic population in the lung lesions, and non-replicating persisters [NRP], associated latent tuberculosis [TB], are the most difficult to kill. Objective. Test the combination of tedizolid, moxifloxacin, and faropenem for activity against NRP using Mtb SS18b in the hollow fiber model [HFS-TB]. Methods. Tedizolid and moxifloxacin were tested as, first, two-drug combination against log-phase growth [LPG], and second, slowly replicating bacilli [SRB] under acidic condition, and with faropenem to create a three-drug combination regimen. Finally, standard regimen [isoniazid-rifampin-pyrazinamide] was used as comparator in the HFS-TB experiment with NRP Mtb. HFS-TB units were sampled for drug-concentration measurement as well as for estimation of bacterial burden using solid agar and mycobacterial growth indicator [MGIT] method. Linear regression was used to calculate the kill slopes with each treatment regimen and analysis of variance [ANOVA] to compare the regimen. Results. Tedizolid at standard dose in combination with high dose moxifloxacin killed 3.05 log10 CFU/mL LPG Mtb and 7.37 log10 CFU/mL SRB in the bactericidal and sterilizing activity HFS-TB experiments, respectively. There was no statistical difference between tedizolid-moxifloxacin-faropenem combination with the standard regimen as both killed 7.35 log10 CFU/mL NRP Mtb in 21 days. There was no emergence of resistance to any of the drugs studies in the three HFS-TB experiment. Conclusion. The experimental regimen of tedizolid, moxifloxacin, and faropenem could effectively kill NRP population of Mtb, and given efficacy against different metabolic population of Mtb could serve as a pan-TB regimen. Clinical studies are warranted to validate the in vitro findings.